Pengaruh Profitabilitas, Capital Intensity, Ukuran Perusahaan, dan Sales Growth Terhadap Agresivitas Pajak - Marcel Ruly Pratama; Purwantoro; Melati Oktafiyani; Lilis Setyowati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to identify the impact of capital intensity, company size, profitability and sales growth on tax aggressiveness in consumer non-cyclical sector companies listed on the IDX during the period 2020 to 2023. This type of research is quantitative, with secondary data obtained from the company's financial statements. The population in this research is consumer non-cyclical sector companies listed on the IDX for the period 31 December 2023. There are 125 companies in the study's population. During the study period, 152 data points were sampled using the purposive sampling method. Data analysis technique using panel data regression using Eviews version 12. The results capital intensity variable has an effect on tax aggressiveness. While profitability, company size, and sales growth do not have an effect on tax aggressiveness.